2020
DOI: 10.13057/biodiv/d211062
|View full text |Cite
|
Sign up to set email alerts
|

Penja fish (Genus: Sicyopterus) from Karama River, West Sulawesi, Indonesia: Growth Pattern and Habitat Characteristics

Abstract: Sicydiinae gobies have been widely collected and identified throughout tropical indo-pacific, except in Karama River, Mamuju, West Sulawesi, Indonesia. Penja was the Gobi fish’s local name, where the pelvic disc is adherent to the belly. This study aims to describe the habitat and growth patterns of genus Sicyopterus in Karama river, which passes through three sub-districts from upstream to downstream. The research was conducted in Karama River from four sites: Kalumpang, Bonehau, Arassi, and Kalonding. Fish g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…Water quality parameters may also play an indirect role in S. auxilimentus movement due to the influence of fluctuating conditions on the distribution of prey species. Water conditions of Laine waterfall, Sangihe island, such as salinity 3.5 psu, temperature 23-25°C, and dissolved oxygen 7.7-9.2 mg/l, were ideal for S. auxilimentus habitat (Bell and Brown 1995;Ellien et al 2011;Keith et al 2011a;Watanabe et al 2014;Muthiadin et al 2020). Future research, incorporating long-term trends with these short-term results, would help form a more complete understanding of the degree to which environmental parameters influence movement of the species.…”
Section: Contemporary Records and Their Habitatmentioning
confidence: 99%
“…Water quality parameters may also play an indirect role in S. auxilimentus movement due to the influence of fluctuating conditions on the distribution of prey species. Water conditions of Laine waterfall, Sangihe island, such as salinity 3.5 psu, temperature 23-25°C, and dissolved oxygen 7.7-9.2 mg/l, were ideal for S. auxilimentus habitat (Bell and Brown 1995;Ellien et al 2011;Keith et al 2011a;Watanabe et al 2014;Muthiadin et al 2020). Future research, incorporating long-term trends with these short-term results, would help form a more complete understanding of the degree to which environmental parameters influence movement of the species.…”
Section: Contemporary Records and Their Habitatmentioning
confidence: 99%
“…Benthic algae of these two types are often found attached to rocks. The bedrock in fast-flowing river waters is a suitable growing medium for these two types of benthic algae and other species from the Bacillariophyceae class [35]. This makes rocky waters and fast currents the primary habitat preferences of the green riffle goby and other gobiid fishes [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…The pectoral fins are black with white bands at the edges, and there is a hint of orange with red and blue stripes at the tip of the dorsal and ventral caudal fins. As a comparison, Muthiadin et al (2020) reported that the body shape of S. longifilis is fusiform and elongated with whitish brown coloration and seven-eight black bands on the body. Although they did not report the results of tracking the morphology of males and females adults separately, the ventral margin of the eye of S. longifilis is marked with triangular black to the posterior end of the mouth.…”
Section: Discussionmentioning
confidence: 99%